65 years of the Department of Belarusian Studies at the University of Warsaw: A Commemorative Volume - Agnieszka Goral (Zeszyty Cyrylo-Metodiańskie)
A review of: Kaleta, Radoslaw, ed. Discovering Belarus...: On the Occasion of the 65th Anniversary of Belarusian Studies at the University of Warsaw. Warsaw University Press, 2023. ISBN 978-83-235-6266-5, 325 pp. [In Polish: Kaleta, Radosław, red. Odkrywając Białoruś... 65-lecie białorutenistyki na Uniwersytecie Warszawskim. Warszawa: Wydawnictwo UW, 2023.] Original title in Polish: Jubileuszowa publikacja Katedry Białorutenistyki Uniwersytetu Warszawskiego.